Multiscale 3D genome rewiring during PTF1A-mediated somatic cell reprogramming into neural stem cells - Rong Zhang; Jun Sun; Shuting Liu; Junjun Ding; Mengqing Xiang (Communications Biology)
Abstract The genome is intricately folded into chromatin compartments, topologically associating domains (TADs) and loops unique to each cell type. How this higher-order genome organization regulates cell fate transition remains elusive. Here we show how a single non-neural progenitor transcription factor, PTF1A, reorchestrates the 3D genome during fibroblast transdifferentiation into neural stem cells (NSCs). Multiomics analyses integrating Hi-C data, PTF1A and CTCF DNA-binding profiles, H3K27ac modification, and gene expression, demonstrate that PTF1A binds to subTAD boundaries subsequently associated with elevated CTCF binding and enhanced boundary insulation, and reorganizes chromatin loops, leading to gene expression changes that drive transdifferentiation into NSCs. Moreover, PTF1A activates enhancers and super-enhancers near low-insulation boundaries and modulates H3K27ac deposition, promoting cell fate transitions. Together, our data implicate an involvement of 3D genome in transcriptional and cell fate alterations, and highlight an essential role for PTF1A in gene expression control and multiscale 3D genome remodeling during cell reprogramming.